(untitled) (Emancipação, 2016)
This article aims to analyze the actions of the National Program for the Promotion of Access to the World of Work (ACESSUAS JOB) from the perspective of social assistance network professionals in the city of Sobral (CE), from their experiences. It presents the results of an exploratory research of analytical nature, conducted with ten professionals of the network, through the use of questionnaires and conducting focus group. Corroborating empirical evidence presents theoretical reflections borrowing ideas from authors such as Araujo and Lima (2014), Colombo (2009), Lima (2010), among others, and the use of documentary research. Results showed satisfactory action of implementation of the program objectives, barriers in coordination and planning of actions, the need for other actions to include users with low education and further actions of the Productive Inclusion Agency as physical reference space for referral of qualified users the world of work.